Compósitos de poliéster reforçados com fibra de vidro : efeito da adição de pó de coco nas propriedades mecânicas, morfologia e custos - Silva, Anderson Ezequiel (2013)
The excessive quantity of byproduct coconut powder as result of processing of coconut fiber, aimlessly industrial application. The objective of this dissertation was the development of composites reinforced with fiberglass using two types of matrices: a pure matrix composite and matrix polyester modified with coir dust. Reducing the size of the coir dust was performed by processing in a ball mill resulting in upper production of particles that crossed off 200 mesh. The composites reinforced with fiberglass and polyester matrix were produced include 10% coir dust (percentage by weight). The viscosity of the pure polyester matrix increased from 244 cP to 480 cP with the addition of coir dust. The step up in viscosity not impair processing of composites, for the reinforcement (fiberglass) was incorporated satisfactorily the two matrices: pure polyester and polyester with coir dust. The mechanical properties were examined through tensile test, three point flexion and IZOD impact. The results of tensile testing of composites reinforced with glass fiber produced with pure polyester matrix and the polyester matrix with coir dust had similar properties. The addition of coconut fiber to matrix produced no change in its performance. Flexion tests showed a 40% reduction in resistance of the polyester matrix composites with coir dust relative to pure polyester matrix composites. The IZOD impact test showed similar results in composites with both types of arrays. There was a 10% reduction in production costs of polyester matrix composites with coir dust, inputs purchased on the overseas market